Rancang Bangun Sistem Informasi Kepegawaian dan Penilaian Kinerja Berbasis Web (Studi Kasus PT. XYZ) - Suprayoga Prabowo, Daniel Wahyu; Karuniawati, Fardiana (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2021)
Abstract— As the rapid development of science, information and technology, humans are trying to find ways to help and facilitate the completion of their work quickly and efficiently. Due to the development of the information that requires an agency or company must be able to manage it, one of which is managing a large number of company employee data, of course it will be difficult if managing a large number of employee data manually. By using information systems, it is expected to facilitate the performance of agencies or companies in managing employee data at the company quickly and accurately.PT. XYZ is a garment production company that has many employees or employees, the employees consist of various educational backgrounds, and has a variety of years of service, every year rolling employees are held routinely for promotion, moving offices or moving work divisions in the production department. and others, the employee rolling criteria are based on evaluating employee performance within a certain period of time, even to dismiss employees is also seen from their performance appraisal. Referring to the problems above, it should be developed a staffing information system and web-based performance appraisal at PT. XYZ The system built can later be operated in various regions or places using the internet network, because PT. XYZ is not only in one place but there are in some places which are quite far from its headquarters, therefore the system that is built based on the web is considered suitable with the conditions in the field. From the employment information system and web-based performance appraisal at PT. XYZ, can be used as a tool to manage employee data, work attendance, monitoring, and evaluating employee performance. Keywords—: Personnel Information System; Performance assessment; Personnel Staff.